Unusual Clinical Manifestation of Epidermoid Cyst Mimicking Basal Cell Carcinoma: Case Report (International Journal of Medical and Surgical Sciences, 2021)
Epidermoid cyst is a type of cutaneous cyst commonly found in daily practice. The facial area is the most common area for emergence of this benign condition. Simple extirpation is usually performed to remove epidermoid cysts. However, in rare cases, epidermoid cysts can evolve into malignancies such as basal cell carcinoma (BCC) or can mimic them, which adds difficulty when making a proper diagnosis. In cases of doubt, histopathology plays a key role in aiding diagnosis. This case report is about a 33-year-old woman with suspected nodular lesion that mimicked BCC, but after histopathological analysis was confirmed to be epidermoid cyst.
Keywords: Epidermoid cyst; basal cell carcinoma; mimicry; Diferencial Diagnosis